2007
DOI: 10.1016/j.ejphar.2007.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Block of CFTR-dependent chloride currents by inhibitors of multidrug resistance-associated proteins

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a membrane protein that belongs to the same family as multidrug resistance-associated proteins whose main function is to expel xenobiotics and physiological organic anions from the cell interior. Despite the overall structural similarity with these membrane proteins, CFTR is not an active transporter but is instead a Cl − channel. We have tested the ability of known inhibitors of multidrug resistance-associated proteins to affect CFTR Cl − curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…One possible explanation is that TMEM16A is not the intestinal CaCC. Benzbromarone was previously identified as a CFTR blocker in Fischer rat thyroid cells (56). Here, in NHBE cells, we found that benzbromarone does not significantly affect CFTR current.…”
Section: Discussionsupporting
confidence: 40%
“…One possible explanation is that TMEM16A is not the intestinal CaCC. Benzbromarone was previously identified as a CFTR blocker in Fischer rat thyroid cells (56). Here, in NHBE cells, we found that benzbromarone does not significantly affect CFTR current.…”
Section: Discussionsupporting
confidence: 40%
“…We first tested the system by using a compound that binds within the CFTR channel pore (at the interface between the two TMDs) and to see whether it could block cross-linking of mutant I340C(TM6)/S877C(TM7) Cys-less/V510A CFTR. Benzbromarone is a CFTR inhibitor that blocks channel activity by occupying the pore (18). Accordingly, HEK 293 cells expressing mutant I340C(TM6)/ S877C(TM7) Cys-less/V510A CFTR were preincubated with various concentrations of benzbromarone and then treated with M11M cross-linker.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies in mice showed that INH 1 (3 mg/kg) reduced 40% of cholera toxin-induced intestinal fluid secretion, whereas INH 2 had no effect (Muanprasat et al, 2007). Finally, inhibitors of multidrug resistanceassociated proteins, among them sulfinpyrazone, probenecid, and benzbromarone, inhibit CFTR activity with low affinity, i.e., K i values of 191, 1244, and 11.5 M, respectively (Diena et al, 2007). This latter observation is nevertheless interesting because it confirms pharmacological similarities within members of the family of ABC transporters.…”
Section: Discussionmentioning
confidence: 99%